Rahnella sp., a Dominant Symbiont of the Core Gut Bacteriome of Dendroctonus Species, Has Metabolic Capacity to Degrade Xylan by Bifunctional Xylanase-Ferulic Acid Esterase - Pineda-Mendoza, Rosa María; Zúñiga, Gerardo; López, María Fernanda; Hidalgo-Lara, María Eugenia; Santiago-Hernández, Alejandro; López-López, Azucena; Orduña, Flor N. Rivera; Cano-Ramírez, Claudia (Frontiers in Microbiology, 2022)
Rahnella sp. ChDrAdgB13 is the main member of the gut bacterial core of Dendroctonus species, one of the most destructive pine forest bark beetles. The objectives of this study were to identify in Rahnella sp. ChDrAdgB13 genome the glycosyl hydrolase families involved in carbohydrate metabolism and specifically, the genes that participate in xylan hydrolysis, to determine the functionality of a putative xylanase-ferulic acid esterase (R13 Fae) and characterize it molecularly and biochemically. The carbohydrate-active enzymes prediction on the genome of this bacterium revealed 25 glycoside hydrolases, 20 glycosyl transferases, four carbohydrate esterases, two auxiliary activities, one polysaccharide lyase and one carbohydrate-binding module (CBM). The R13 Fae predicted showed amino acid identity of 67.8–99.9% to the putative esterases and glycosyl hydrolases from Rahnella species and some members of the Yersiniaceae family. The r13 fae has an ORF of 1,182 bp, encoding for 393 amino acids (43.5 kDa), a theoretical pI of 5.94, a signal peptide of 26 amino acids, carbohydrate esterase catalytic domain, and CBM48. Docking showed that R13 Fae presents a higher binding affinity to ferulic acid, α-naphthyl acetate and arabinoxylan with ARG371 bonded by a hydrogen bridge, and low binding affinity to starch. The R13 Fae recombinant protein showed activity on α-naphthyl acetate and xylan, but not on starch. The R13 Fae characterization using xylan as substrate showed an optimal activity at pH 6.0 and 25ºC, with a specific activity of 0.1 U mg-1, was stable at pH from 4.5-9.0, retaining nearly 66-71% of its original activity, and exhibited a half-life of 23 days at 25ºC. The Km and Vmax for enzyme was 14 mg ml-1 and 0.598 μmol-1 min-1 mg, respectively, using beechwood xylan. The enzyme was stable in the presence of metallic ions, except for Hg2+. The products of R13 Fae mediated hydrolysis of beechwood xylan were xylobiose and xylose, manifesting an exo-activity. The results suggest that Rahnella sp. ChDrAdgB13 hydrolyse xylan and its products could be assimilated by its host and other gut microbes as a nutritional source, demonstrate their functional role in the bacterial-insect interaction contributing to their fitness, development, and survival.